1989
DOI: 10.1007/bf01261467
|View full text |Cite
|
Sign up to set email alerts
|

Pl�doyer f�r die prim�re Resektion mit prim�rer Anastomose bei der komplizierten Sigmadiverticulitis

Abstract: Of the 107 patients with complicated diverticulitis operated from 1973-1986 47 were females and 60 males. In 14 of the 107 patients a perforated diverticulitis with diffuse purulent/faecal peritonitis was found, a perforated diverticulitis with localized purulent peritonitis/paracolic abscess in 68 patients and an acute phlegmonous diverticulitis without perforation in 25 patients. Additional pathologic findings were internal fistulae (13 patients), necrotizing fasciitis (3 patients), obstruction (3 patients) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
6
0
5
Order By: Relevance
“…Therefore, comparison of the different studies and their results is quite difficult. In the recent literature, there seems to be a change in the surgical treatment of complicated diverticulitis in the last 10–15 years in the direction of primary anastomosis and away from the Hartmann procedure [2, 3, 13]. This has been the standard treatment before in all cases with acute left colonic diverticulitis [26, 27], because the risk of an anastomosis in the presence of acute inflammation was believed to be too high [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, comparison of the different studies and their results is quite difficult. In the recent literature, there seems to be a change in the surgical treatment of complicated diverticulitis in the last 10–15 years in the direction of primary anastomosis and away from the Hartmann procedure [2, 3, 13]. This has been the standard treatment before in all cases with acute left colonic diverticulitis [26, 27], because the risk of an anastomosis in the presence of acute inflammation was believed to be too high [20].…”
Section: Discussionmentioning
confidence: 99%
“…August and Wise [7]and Alanis et al [8]were able to show that a colostomy is not absolutely necessary even in cases of pericolonic abscess, localized pelvic abscess and mesenteric phlegmone, but usually is in generalized purulent or fecal peritonitis. In a review of the recent literature, most authors prefer primary anastomosis in patients without large abscess or advanced peritonitis [1, 2, 3, 10, 11, 12, 13, 14, 15], but classification and nomenclature are not used uniformly so that comparison of the results becomes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have suggested that patients undergo ing a direct anastomosis following colonic resection have a better prognosis than patients who undergo a two-stage or a three-stage procedure [5,6], However, such an approach is only suitable in patients in relatively good general condition. When the overall clinical situation is poor, the procedure is Hartmann operation, but a signifi cant mortality has been reported [1.2.…”
Section: Discussionmentioning
confidence: 99%
“…War man viele Jahre der Auffassung, daû die Divertikulose des Kolons, die nahezu bei 70% der 50ja È hrigen beobachtet wird, harmlos ist und daû auch Entzu È ndungen einen positiven Spontanverlauf erleben oder konservativ mit Nahrungskarenz und Antibiose erfolg-reich behandelt werden ko È nnen, so belegen inzwischen vorliegende Daten [4,6,14,15,19,20], daû diese Einscha Ètzung die fu È r den Patienten risikoreichere Variante mit einer Letalita È t von etwa 10% darstellt [4,19,20]. Es ist das Verdienst von Wellmann et al [16], daû uns eine Standortbestimmung bezu È glich Diagnostik, Indikationsstellung und chirurgischer Technik bei der Behandlung der Divertikulitis an deutschen Kliniken aus dem Jahr 1994 mit aus heutiger Sicht zum Teil verblu È ffenden Resultaten vorliegt.…”
Section: Aktueller Stand Der Diskussionunclassified